Successful Laparoscopic Retrieval of an Accidental Intra - Abdominal Sewing Needle – A Case Report - Basukala, Sunil; Thapa, Narayan; Rana Magar, Sushil; Bahadur Rayamajhi, Bikash; Raj Gautam, Alok; Bhandari, Ravi (Medical Journal of Shree Birendra Hospital, 2022)
Accidental ingestion of sewing needle is a common presentation in daily emergency medical practice but its insertion through the abdominal wall is quite rare. We present a case of 26 years old serving soldier who had an accidental intraabdominal insertion of sewing needle which was managed laparoscopically. Initially patient was asymptomatic, however he complained of lower abdominal pain later. This was followed by successful laparoscopic retrieval of sewing needle located in right iliac fossa with no documented complications during six months of follow-up of the patient.